Dampak Kualitas Produk dan Harga Terhadap Keputusan Pembelian pada Generasi Milenial: Studi Kasus pada Pelanggan Kartu Xl di Kota Gorontalo - Danu Wardana Ali; Tineke Wolok; Ramlan Amir Isa (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aimed to discover the extent to which Product Quality and Price Influence Purchase Decisions among millennials, focusing on XL Card customers in Gorontalo City. The sampling employed in this study was purposive sampling, with a sample size of 100 respondents, which was determined using the Lemeshow formula. Data collection was conducted using questionnaires distributed to the population of XL Card customers in Gorontalo City. The analytical tool used to test this study was multiple linear regression, with data analysis performed using SPSS version 27. The study findings indicated that, partially, Product Quality did not significantly influence Purchase Decisions, with a t-value of 1.023 compared to the critical value of 1.984. Conversely, Price significantly influenced Purchase Decisions, with a t- value of 11.451 exceeding the critical value of 1.984. Furthermore, the simultaneous test results indicated that both Product Quality and Price significantly influenced Purchase Decisions among millennials purchasing XL Cards. The Product Quality and Price variables collectively explained 58.8% of the variance in Purchase Decisions, while the remaining 41.2% can be attributed to other variables not included in this study